Author Correction: Regulatory role of G9a and LSD1 in the Transcription of Olfactory Receptors during Leukaemia Cell Differentiation. Issue 1 (December 2018) - Jung, Hyeonsoo; Chae, Yun-Cheol; Kim, Ji-Young; Jeong, Oh-Seok; Kook, Hoon; Seo, Sang-Beom
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.